2017
DOI: 10.18632/oncotarget.20962
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin enhances skeletal muscle hypertrophy and myoblast differentiation by regulating Prmt7

Abstract: Apigenin, a natural flavone abundant in various plant-derived foods including parsley and celery, has been shown to prevent inflammation and inflammatory diseases. However, the effect of apigenin on skeletal muscle hypertrophy and myogenic differentiation has not previously been elucidated. Here, we investigated the effects of apigenin on quadricep muscle weight and running distance using C57BL/6 mice on an accelerating treadmill. Apigenin stimulated mRNA expression of MHC (myosin heavy chain) 1, MHC2A, and MH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 41 publications
0
37
1
Order By: Relevance
“…The myogenic marker gene Myog significantly interacted with two potential cis regulatory elements at 40 and 80 kb upstream ( Figure 8 B, Table S5 ). Moreover, Igf2 , which regulates skeletal muscle development 13 , 46 , was also found to exhibit higher interaction with imprinted Igf2 / H19 in myotubes than in myoblasts ( Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The myogenic marker gene Myog significantly interacted with two potential cis regulatory elements at 40 and 80 kb upstream ( Figure 8 B, Table S5 ). Moreover, Igf2 , which regulates skeletal muscle development 13 , 46 , was also found to exhibit higher interaction with imprinted Igf2 / H19 in myotubes than in myoblasts ( Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Adipogenic differentiation and myogenic differentiation are essential developmental processes of adipose and skeletal muscle, regulated by complex molecular networks and epigenetic modifications 8 - 11 . Adipogenesis and myogenesis marker genes (e.g., PPARG , CEBPA , and FABP4 in adipocytes, and MRFs and MHC in myotubes) were shown to be activated during differentiation, accompanied by changes in cell morphology (lipid droplet accumulation of adipocytes and fusion of myoblasts into multinucleated myotubes, respectively) 12 , 13 . Adipogenesis- and myogenesis-associated expression of PPARG and FRG1 was found to be regulated by long-range chromatin interactions, respectively, suggesting the modulatory role of spatial chromatin structure in adipogenesis and myogenesis 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…With resveratrol, pro-differentiating activities have also been shown on myoblasts, resulting in the formation of myotubes [ 57 ]. Apigenin has also been shown to promote osteogenic differentiation of human mesenchymal stem cells through JNK and p38 MAPK pathways [ 58 , 59 ], to enhance myoblast differentiation by regulating Prmt7 [ 60 ], to induce granulocytic differentiation in human promyelocytic leukemia HL-60 cells [ 61 ], and to activate morphological differentiation and G2-M arrest in rat neuronal cells [ 62 ]. It has also been reported that apigenin from Croton betulaster Mull inhibits proliferation, induces differentiation and regulates the inflammatory profile of C6 glioma cells [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin is a flavonoid abundantly available in Apium leaves. It reportedly has anti-cancer properties [reviewed by Kowalczyk et al (2017)] and can enhance skeletal muscle hypertrophy and myoblast differentiation in mice (Jang et al, 2017). As aforementioned, the enzyme responsible for conversion of naringenin to apigenin is known and its manipulation leads to an increased level of apigenin (Tan et al, 2017).…”
Section: Breeding For Nutraceuticals and Food Safetymentioning
confidence: 99%